Control of Constrained Linear-Time Varying Systems via Kautz Parametrization of Model Predictive Control Scheme - Massoud Hemmasian Ettefagh; José De Doná; Mahyar Naraghi; Farzad Towhidkhah (Ital Publication, 2017)
Kautz parametrization of the Model Predictive Control (MPC) method has shown its ability to reduce the number of decision variables in Linear Time Invariant (LTI) systems. This paper devotes to extend Kautz network to be used in MPC Algorithm for linear time-varying systems. It is shown that Kautz network enables us to maintain a satisfactory performance while the number of decision variables are reduced considerably. Stability of the algorithm is studied under the framework of the optimal solution. The proposed method is validated by an illustrative example. In this regard, the performance of unconstrained systems as well as constrained ones is compared.